Qualitative Researcher Vulnerability Negotiating, Experiencing and Embracing - Clift, Bryan C.; Costas Batlle, Ioannis; Bekker, Sheree; Chudzikowski, Katharina (Taylor & Francis, 2023)
Qualitative Researcher Vulnerability provides conceptual, experiential, and practical insights into the vulnerability of the qualitative researcher. Compared to participants' vulnerability, researcher vulnerability has seen limited attention in the qualitative research process, but yet it is an important consideration. Drawing on an interdisciplinary group of authors-across criminology, education, feminisms, geography, health, kinesiology, nursing, management and organisation, policy, political science, psychology, sociology, and qualitative inquiry writ broad-the book explores the ways in which we might understand and work with researcher vulnerability, most notably in relation to ethics, risk, empathy, emotion, and power. Ultimately, the authors suggest researcher vulnerability is a vital component of our research practices throughout the research process, for emerging as well as experienced researchers. Whilst researcher vulnerability can be something to protect against, it is also something to be aware of, explore, learn from, work with, and at times (and with care and consideration) embrace. This book is suitable for undergraduate, postgraduate students, and emerging and established researchers who are utilising qualitative research. It will be especially useful for researchers examining (potentially) sensitive topics, or for those who wish to develop more responsive, responsible, ethical, or reciprocal approaches to qualitative practices.